The extent to which the requirements of the international standard (ISO-9001 / 2008) are met and their impact on the product (A survey sample of the opinions of a sample of employees at the Al-Mamoun factory which manufactures the De Luxe soap product) (Al-Mansour Journal, 2025)
The importance of the international specifications ISO (ISO - 9001/2008) through the product in the safe factory for manufacturing laundry soap (De Luxe brand) through the application of the ISO version in an effective and precise application in order to promote this required product with the quality performance in production of this agreed upon product is (De Luxe laundry soap) to be a high-quality product to be presented to customers.The quality of the product is due to the organization in consolidating itself in the market to achieve a high level of quality to satisfy customers and obtain new customers and a geographical area in the local market for the purpose of controlling some of the challenges that it may face in the future. The research population consists of all workers in the Al-Maamoun factory for manufacturing soap (De Luxe). The community sample is (100), and because the research is based on an exploratory study of the opinions of a group of workers, the random research sample was represented by workers in the Al-Maamoun factory for manufacturing laundry soap (De Luxe brand), and it was determined the sample size included in the questionnaire, according to Stephen Thompson’s equation, amounted to (50) workers. The research consisted of four sections, including the first section (the methodology of scientific research and some previous studies), the second section (theoretical variables, including the ISO 9001/2008 version) and the product), and the third section (the applied section and the results of statistical analysis). The fourth section was (conclusions and recommendations) in addition to the sources. Arabic and foreign.
Keywords: Availability of ISO requirements for the product in the organization